Consonant Change in Cognates Shared by Indonesian and Palembang Malay - Fauzi Syamsuar (Badan Pengembangan dan Pembinaan Bahasa, 2021)
This article describes the phenomena of sound changes, i.e., changes of single segmental sound of consonants, found in cognates shared by Indonesian and Palembang Malay. A list containing 2,535 cognates shared by Indonesian and Palembang Malay becomes the corpus. Since Indonesian is a modern language derived from Standard Malay, it becomes the reference language in the efforts of descriptions. Consonant strengthening, fortition, consonant weakening, lenition, and glottalization become the phenomena found in the consonant changes. Various syllabic structures in which the consonants distributed are also described. The differences of productivity of certain consonant-changes compared to others are found. The productivity shows that, compared to Indonesian, the occurrences of weaker consonants lenis consonants are more productive in Palembang Malay. AbstrakArtikel ini membahas gejala penggantian bunyi, yakni penggantian bunyi-segmental konsonan tunggal, yang didapati dalam kognat atau kata seasal yang dimiliki bersama oleh bahasa Indonesia dan bahasa Melayu Palembang. Sebuah daftar yang memuat 2.535 kognat dalam bahasa Indonesia dan bahasa Melayu Palembang menjadi korpus. Karena merupakan bahasa modern yang terderivasi dari bahasa Melayu Baku, bahasa Indonesia menjadi bahasa acuan dalam pembahasan. Penguatan konsonan, fortisi, pelemahan konsonan, lenisi, dan glotalisasi menjadi gejala yang didapati dalam penggantian konsonan. Struktur suku kata yang di dalamnya konsonan tersebut di atas terdistribusi juga dibahas. Didapati perbedaan produktivitas gejala penggantian konsonan tertentu dibandingkan dengan gejala yang lain. Produktivitas itu menunjukkan bahwa jika dibandingkan dengan bahasa Indonesia, kehadiran konsonan lemah atau konsonan lenis lebih produktif dalam bahasa Melayu Palembang.